2014
DOI: 10.1177/1457496914532249
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Recreational Alpine Skiing and Snowboarding Injuries: six years experience in the largest ski resort in Finland

Abstract: Background and Aims: the aim of this study was to provide information on incidences and severity of recreational alpine skiing and snowboarding injuries in northern finland and to discuss possible preventive measures to reduce the number and severity of injuries in the future.Materials and Methods: this retrospective study consists of all injured skiers and snowboarders in the levi Ski Resort during the 2006-2012 winter seasons. the levi Ski Resort has a SkIdata ® system which records automatically every ski-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…His findings suggest that Skiers had a relatively stable injury incidence during this period of time, and the number of Snowboard injuries had increased significantly, due to the rise in Snowboard's popularity. Meanwhile in Europe, Stenroos & Handolin (2015) brought to us injury incidence data from Finland, collected from 2006 to 2012's winter seasons. The data showed that the most common injuries affect the knee in skiers, and the upper extremity, especially the wrist, in snowboarders.…”
Section: Introductionmentioning
confidence: 99%
“…His findings suggest that Skiers had a relatively stable injury incidence during this period of time, and the number of Snowboard injuries had increased significantly, due to the rise in Snowboard's popularity. Meanwhile in Europe, Stenroos & Handolin (2015) brought to us injury incidence data from Finland, collected from 2006 to 2012's winter seasons. The data showed that the most common injuries affect the knee in skiers, and the upper extremity, especially the wrist, in snowboarders.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with the literature when it comes to both recreational and competitive skiers. 14,31,64,107,118…”
Section: Injury Profilementioning
confidence: 99%
“…Head and neck injury rates per 1000 participants per year were estimated at 0.95 among skiers and 2.48 among snowboarders [18]. Kim et al reported the most common injuries among snowboarders were wrist injuries, while the most common skiing injuries occurred to the lower extremities, predominantly affecting the anterior cruciate ligament (ACL) [74,75]. In addition, a 6 year retrospective study assessing injured recreational alpine skiers and snowboarders at the Levi Ski Resort in Finland found an average injury incidence of 0.98 injuries per 10,000 lift runs, with knee injuries to skiers constituting nearly one third of all cases, while snowboarders sustained more injuries to the upper extremities, primarily the wrist [75].…”
Section: Ski and Snowboard Injuriesmentioning
confidence: 99%
“…Kim et al reported the most common injuries among snowboarders were wrist injuries, while the most common skiing injuries occurred to the lower extremities, predominantly affecting the anterior cruciate ligament (ACL) [74,75]. In addition, a 6 year retrospective study assessing injured recreational alpine skiers and snowboarders at the Levi Ski Resort in Finland found an average injury incidence of 0.98 injuries per 10,000 lift runs, with knee injuries to skiers constituting nearly one third of all cases, while snowboarders sustained more injuries to the upper extremities, primarily the wrist [75]. These estimates reflect the predominance of upper extremity injuries among snowboarders and lower extremity injuries among skiers with participants in both activities susceptible to head and neck injuries.…”
Section: Ski and Snowboard Injuriesmentioning
confidence: 99%